1995
DOI: 10.1007/bf01922437
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of methionine-enkephalin, somatostatin and insulin on cultured gonadal cells of the snailHelix aspersa

Abstract: Isolated snail gonadal cells were cultured in the presence of synthetic neuropeptides in order to determine the subsequent effect of these substances on gonadal synthetic activities. Gonadal cells were incubated for 24 h in concentrations of methionine-enkephalin, somatostatin and insulin ranging from 10(-4) M to 10(-9) M, in medium 199 supplemented with 6% Ultroser G. Synthesis of DNA and protein by the cultured cells were simultaneously estimated by measuring incorporation of 3H thymidine and 35S methionine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Molluscan insulin-related peptide is a growth stimulating hormone related peptide involved in glucose metabolism and growth ( Ebberink et al, 1989 ). It may also participate in the regulation of germinal cell proliferation and maturation ( Monnier and Bride, 1995 ). Molluscan insulin-related peptides have been determined in the snail L. stagnalis ( Smit et al, 1988 , 1996 ; Li et al, 1992b ), limpet L. gigantea ( Veenstra, 2010 ), and slugs A. californica ( Floyd et al, 1999 ) and D. reticulatum ( Ahn et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Molluscan insulin-related peptide is a growth stimulating hormone related peptide involved in glucose metabolism and growth ( Ebberink et al, 1989 ). It may also participate in the regulation of germinal cell proliferation and maturation ( Monnier and Bride, 1995 ). Molluscan insulin-related peptides have been determined in the snail L. stagnalis ( Smit et al, 1988 , 1996 ; Li et al, 1992b ), limpet L. gigantea ( Veenstra, 2010 ), and slugs A. californica ( Floyd et al, 1999 ) and D. reticulatum ( Ahn et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…These neuropeptides are involved in the growth and glucose metabolism (Ebberink et al 1989). They also play a role in mediating germinal cell proliferation and maturation (Monnier & Bride 1995). Three insulin-like precursors (Insulin-like 2A, 2B, and MIP-related peptide) were identified in H. discus hannai.…”
Section: Insulin-related Peptidementioning
confidence: 99%
“…The involvement of ILPs in the regulation of carbohydrate metabolism has also been reported in invertebrates, such as Lymnaea stagnalis [ 41 ] and Aplysia californica [ 3 ]. In this study, the relatively greater abundance of Sj ILP mRNA transcript in the pancreas suggests the paracrine function of insulin-like peptides during digestion ( Figure 7 A) [ 16 ]. In mollusks, neurosecretory cells in the cerebral ganglia are the main source of ILPs [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 93%
“…In Planorbarius corneus [ 14 ] and Lymnaea stagnalis [ 6 ], ILPs have been detected in the brain and are involved in the hormonal control of reproduction [ 15 ]. In isolated gonadal cells of Helix aspersa , Monnier and Bride [ 16 ] showed that vertebrate insulin stimulated protein synthesis, suggesting that ILPs may be involved in the regulation of germinal cell proliferation and maturation. In the Pacific oyster Crassostrea gigas , Cg- ILP is mainly expressed in the gonadal area, suggesting involvement in the control of sexual reproduction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%